Suppression of oxygen toxicity by melatonin - Reiter Russel J; Tan Dun-Xian; Qi Wen-Bo (Acta Pharmacologica Sinica, 2016)
Melatonin, the chief secretory product of the pineal gland, was recently found to be a free radical scavenger and antioxidant. While most studies to date have used pharmacological quantities of melatonin to limit oxidative damage, physiologic concentrations of the indole which are present in aerobic organisms have also been shown to resist molecular damage inflicted by free radicals. Melatonin has several functions in terms of its antioxidative ability. It readily scavenges the most highly toxic free radical, the hydroxyl radical, and it directly detoxifies the peroxynitrite anion, nitric oxide, singlet oxygen, and the peroxyl radical. Precisely how efficient melatonin is in neutralizing each of these toxic agents remains to be determined. Melatonin also may stimulate several antioxidative enzymes including superoxide dismutase, glutathione peroxidase, and glutathione reductase as well as inhibiting the pro-oxidative enzyme, nitric-oxide synthase. Finally, melatonin chelates transition metal ions and prevents the deterioration of cellular membranes. This combination of actions may all contribute to melatonin's ability to reduce oxidative damage. Melatonin is highly effective in reducing nuclear DNA damage and membrane lipid destruction due to toxic free radicals in vivo. These findings have implications for disease processes, eg, neurodegenerative and cardiovascular diseases, which involve free radicals and for aging itself, which also is believed to be related to accumulated oxidative damage.